Impacto del bono de desarrollo humano en la reducción de la pobreza en la parroquia el rosario del cantón el empalme año 2023. - Avila Quiroz, Dalimber Daniel (2025)
This research project on the impact of the Bono de Desarrollo Humano focuses on analyzing how this conditional cash transfer program has influenced improvements in the quality of life of beneficiaries, it aims to analyze the impact of the Bono de Desarrollo Humano on poverty reduction in the parish El Rosario of the canton El empalme year 2023, A qualitative-quantitative methodology will be applied, using a mixed approach, to analyze the effects of the voucher on key indicators such as food security, access to education and health, as well as improved housing conditions. The findings indicate that the Bono de Desarrollo Humano has had a significant impact on the reduction of poverty, allowing beneficiaries to cover their basic needs and develop small enterprises. However, the research also points to persistent challenges, such as lack of training in resource management and limited access to comprehensive services that enhance the impact of the voucher. Therefore, policies aimed at strengthening training and support for beneficiary families are proposed in order to maximize the impact of the Bono de Desarrollo Humano promote sustainable development in the parish. This study offers a valuable perspective on the effectiveness of social policies in the fight against poverty in specific local contexts.